Comparative assessment of structural changes in the prostate after bipolar plasma and thulium fiber laser enucleation of benign prostatic hyperplasia - I. K. Notov; S. V. Zalavina; S. V. Mashak; N. P. Bgatova; S. V. Pozdnyakova; S. V. Savchenko; K. G. Notov (Acta Biomedica Scientifica, 2024)
Background. Benign prostatic hyperplasia (BPH) is a common disease in older men. Transurethral surgery in BPH is the gold standard for treatment, but the techniques differ in the energy used. Considering the different mechanisms of action of bipolar plasma and thulium fiber laser energy on prostate tissue, the study of structural changes under their influence is relevant.The aim. To study the features of structural changes in the prostate during bipolar plasma and thulium fiber laser enucleation of benign prostatic hyperplasia.Methods. Thirty one patients with BPH were divided into two groups. Group 1 (n = 17) underwent transurethral plasma enucleation of the prostate; Group 2 (n = 14) underwent transurethral thulium fiber laser enucleation. Fragments of the surgical prostate capsule were collected intraoperatively and were processed according to standard examination protocols using light and electron microscopy. The width of coagulation necrosis, the relief of the dissection line, the severity of cell and the prostate intercellular matrix destruction were taken into account.Results. Studies have shown the clinical and functional perioperative homology of the compared methods of surgical treatment of BPH. Data from light and electron prostate microscopy showed a greater damaging effect of bipolar plasma energy, which is manifested by a larger width of the zone of coagulation necrosis, a torn and raised appearance of the dissection line, and pronounced integrity violations of cellular elements and intercellular matrix components. Laser exposure causes less pronounced changes, which indicates a more gentle effect of the thulium fiber laser on the prostate components.Conclusion. The obtained microscopy results indicate that the intraoperative action of a thulium fiber laser is less traumatic for the cells and intercellular matrix of the surgical prostate capsule compared to bipolar plasma exposure.